IMPROVING THE PERFORMANCE OF VILLAGE SECRETARY ON THE BASIS OF TRAINING, FINANCIAL INCENTIVE, MONITORING AND EVALUATION (A case study in village government in Demak district) - Sukarman Sukarman; Widiyanto Widiyanto (IJIBE (International Journal of Islamic Business Ethics), 2017)
The present study aimed to test a model in which training predicts professional competence and village secretary performance that were moderated by financial incentives and monitoring and evaluation. A total of 164 respondents from the village government office of Demak district completed questionnaires on training, professional competence, financial incentives, monitoring and evaluatiion, and village secretary performance. The results from structural equation modeling based on smartPLS 3.0 confirmed that 1) training was positively related to professional competence and village secretary performance; 2) professional competence was positively related to village secretary performance; and 3) financial incentives and monitoring and evaluation moderated the relationships between training and village secretary performance.